Assessment Model of Contractor Quality Management Maturity - Franciska Lisa Permatasari; Tri Joko Wahyu Adi; I Putu Artama Wiguna (IPTEK Journal of Proceedings Series, 2017)
One of the most important parts of a project management is the quality management. While it is absolutely necessary to conduct a thorough research on the maturity of quality management in construction companies, especially contractors so that construction companies know at what level of their company quality, this has an effect on building customer perceptions of their companies and the business of the company itself to continue to grow to be able to reach the highest maturity level. This paper aims to propose an assessment model of contractor quality management maturity (QMM) that covers both the corporate and project levels of a construction project. Determination of research variables was conducted with the study of literature in depth and validated by experts. Weighting variables by pairwise comparison method were based on interviews with experts and was represented in the form of a spider web. For model validation, case studies of large state-owned contractors and a medium-sized private contractor in Surabaya were used. The weighting for QMM assessment on contractors is 43% on corporate level and 57% on project level. In corporate level there are 10 variables with each weighting: People and Customer Management (2.9%), Supplier Partnership (1.6%), Communication of Improvement Information (2.4%), Customer Satisfaction Orientation (5.3%), External Interface Management (1.4%), Strategic Quality Management (6.2%), Team Work Structures for Improvement (4.3%), Operational Quality Planning (4.4%), Quality Improvement Measurement System (8.2%), and Corporate Quality Culture (6.3%). Project level quality consists of 39% for product quality and 18% for service quality. In the project level there are 8 variables for product quality: Performance (9.0%), Features (4.1%), Reliability (8.0%), Conformance (5.6%), Durability (4.5%), Serviceability (3.0%), Aesthetics (1.7%), Perceived Quality (3.1%). While the service quality consists of 5 variables: Service Reliability (4.9%), Responsiveness (2.7%), Assurance (5.7%), Emphaty (1.8%), and Tangibles (2.8%).